2016
DOI: 10.1007/978-1-4939-2981-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pile-Driving Sounds on the Survival of Larval Fish

Abstract: Concern exists about the potential effects of pile-driving sounds on fish, but evidence is limited, especially for fish larvae. A device was developed to expose larvae to accurately reproduced pile-driving sounds. Controlled exposure experiments were carried out to examine the lethal effects in common sole larvae. No significant effects were observed at zero-to-peak pressure levels up to 210 dB re 1 μPa(2) and cumulative sound exposure levels up to 206 dB re 1 μPa(2)·s, which is well above the US interim crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…Na langdurige blootstelling aan geluid vermindert de stressrespons (Radford et al, 2016). Ook voor zeebaarslarven werd geen verhoogde mortaliteit gevonden als gevolg van heien (Bolle et al, 2014). Potentiële effecten van windparken op het zeebaarsbestand, bijvoorbeeld door vermindering van geschikt habitat, kunnen niet uitgesloten worden.…”
Section: Mogelijke Impact Van Windparkenunclassified
“…Na langdurige blootstelling aan geluid vermindert de stressrespons (Radford et al, 2016). Ook voor zeebaarslarven werd geen verhoogde mortaliteit gevonden als gevolg van heien (Bolle et al, 2014). Potentiële effecten van windparken op het zeebaarsbestand, bijvoorbeeld door vermindering van geschikt habitat, kunnen niet uitgesloten worden.…”
Section: Mogelijke Impact Van Windparkenunclassified
“…Fish mortality after sound exposure has mostly been studied for pile driving (e.g. [8,32,33]). It is generally thought that mortal injuries after sound exposure occur in relatively few individuals, situated close to the sound source.…”
Section: (A) Empirical Sound Exposure Studiesmentioning
confidence: 99%
“…Mortality of fish following exposures to anthropogenic sounds is generally limited to high-intensity impulsive sounds (e.g., explosions, pile driving, airguns; Table 11). Booman et al (1996) data cited as reported in Bolle et al (2016) Of the few studies available that evaluated sub-lethal effects of dredginginduced sounds (i.e., DEFRA 2003;Nedwell et al 2008;Heinis et al 2013), there was no evidence of risk for auditory injury (TTS) or behavioral effects for larger-bodied fish (>2 g). In terms of adverse effects to smaller-bodied fish, Heinis et al (2013) estimated based on "worst case" scenario that smaller-bodied fish (>2 g) were at risk in the immediate vicinity of the sound source (<20 m).…”
Section: Fish Effects Summarymentioning
confidence: 99%